Elaboración de un plan de gestión de residuos sólidos para el distrito de Lobitos, Talara - Aramayo-Bazzetti, Armando (2024)
This research focuses on the presentation of a Solid Waste Management Plan for the district of Lobitos, located in Talara - Piura. The main objectives included carrying out a analysis to evaluate the how things stand locally, characterizing daily household garbage in qualitatively terms and quantitatively too (separated at the source), and developing an appropriate alternative management plan. The study was held out in July 2021, covering a total of 69 houses along 8 consecutive days.The results exposed an average of 1 ton of waste per day, with a breakdown of 39% organic waste, 19% unusable waste, 9% plastics, 9% metals, 9% paper and cardboard, 8% hazardous waste (including fishing nets) and, finally, 7% glass. The average daily volume generated was 4,4 m3, with an average density of 31,624 kg/m3.Based on these results and a survey conducted among public cleaning personnel, insufficiencies were recognized that served as a basis for the formulation of action strategies. These strategies are intended to guide the optimization of waste handling in the area, seeking to improve efficiency and sustainability in waste treatment.